Aktuální stav projektu eduroam v ČR - Kocur, Zbyněk; Vacula, Lubomír; Machula, Vladimír (International Society for Science and Engineering, o.s., 2010)
This article describes the basic lines of the worldwide academic project called Eduroam. The reader is apprised either with the whole history, or the contemporary phase and its further development at the area of the Czech republic.

Tento článek popisuje základní rysy celosvětového akademického projektu eduroam. Čtenář je obeznámen nejen s jeho historií, ale i se současným stavem a jeho dalším vývojem na území ČR.
The Contemporary state of the Eduroam Project in the Czech Republic